Digital Transformation as a Factor in Increasing the Investment Attractiveness of Ukraine in the Context of the Experience of EU Countries - Kiriienko Sergii O. (Bìznes Inform, 2025)
The aim of this article is to examine the relationship between the digital transformation of the economy and the investment attractiveness of countries in the context of global instability and to define strategic guidelines for enhancing Ukraine’s investment potential. The article analyzes the conceptual foundations for the development of the digital economy in global practice, highlights the role of digitalization as a multidimensional factor in structural transformations, particularly in increasing the transparency of market processes, reducing transaction costs, and expanding investment opportunities in innovative sectors. Special attention is given to the experience of European Union countries regarding the integration of digital technologies into the strategic priorities of economic policy and the mechanisms for their implementation at various levels of governance. The article presents a comparative analysis of the state of digital transformation in Ukraine and EU countries, outlining the main discrepancies, weaknesses, and institutional challenges. The article examines the state of internet infrastructure development, the level of digital literacy, the degree of digitalization of small and medium-sized enterprises, the effectiveness of electronic governance systems, and the quality of the regulatory environment. Key barriers hindering the development of the digital economy in Ukraine have been identified, including uneven access to digital technologies, fragmentation of government support for innovative projects, and insufficient integration of digital practices into production processes. A correlation analysis has been conducted to examine the dependencies between the level of digital development (based on the DESI and WDCI indices) and major economic indicators. It is found that in EU countries, digitalization has a complex feedback relationship with traditional economic indicators, particularly with the inflow of foreign direct investments and unemployment rates, indicating the maturity of digital markets. In contrast, in Ukraine, a positive correlation is observed between the development of digital competitiveness, GDP growth, and the inflow of foreign investments, which confirms the potential of digitalization to serve as a catalyst for economic recovery in the post-crisis period. A comparative characterization of digital development is proposed, and directions for priority measures to stimulate digitalization in Ukraine are substantiated. The article substantiates the necessity of building broadband infrastructure, developing digital literacy among the population, implementing targeted State programs to support digital startups and high-tech enterprises, and harmonizing legislation in the field of cybersecurity according to EU standards. It is emphasized the importance of developing digital competencies, activating entrepreneurial initiative in the innovative sector, and attracting foreign investment in digital technologies. The role of human capital as a key determinant of successful digital transformation of the economy is underscored, and its significance for shaping a competitive investment environment is emphasized. It is found that only a systematic, comprehensive, and strategically balanced approach to digitization can ensure the long-term economic resilience of Ukraine, contribute to strengthening its positions in the global digital economy, and transform it into one of the promising players in the European innovation space.